2009
DOI: 10.1007/978-1-60761-362-6_30
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cells in Human Pregnancy

Abstract: Natural killer (NK) cells account for 70% of the leukocytes in the mucosal lining of the uterus (the decidua) in the first trimester of pregnancy. They are CD56(superbright) granulated cells expressing a repertoire of Killer-cell Immunoglobulin-like Receptors (KIR) skewed towards recognising HLA-C, which is the only classical class I MHC found on placental trophoblast cells. The function of decidual NK cells is not yet known, but there is evidence to suggest that they are involved in mediating trophoblast inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…04/Q0108/23; Cambridge, United Kingdom), and informed written consent was obtained from each patient. Trophoblast cells and leukocytes were isolated as previously described (58).…”
Section: Methodsmentioning
confidence: 99%
“…04/Q0108/23; Cambridge, United Kingdom), and informed written consent was obtained from each patient. Trophoblast cells and leukocytes were isolated as previously described (58).…”
Section: Methodsmentioning
confidence: 99%
“…KIRs are involved in susceptibility to diseases, such as celiac disease [6], rheumatoid arthritis [7], systemic lupus erythematosus [8], and infectious diseases [9]. KIRs also play a role in the process of pregnancy [10], the potentially beneficial graft versus leukemia responses [11], and the HLA-matched hematopoietic cell transplantation [12]. Recent studies have also revealed that KIR polymorphism in patients with leukemia is correlated with susceptibility to this disease [46] and that the NK cell can be used for leukemia immunotherapy [47].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, KIRs may play a significant role in the control of immune responses [5]. KIRs have been found to be implicated in susceptibility to diseases, including celiac disease [6], rheumatoid arthritis [7], systemic lupus erythematosus [8], and infectious diseases [9], in the process of pregnancy [10], in the potentially beneficial graft versus leukemia responses after allogeneic transplantation [11], and in the HLAmatched hematopoietic cell transplantation [12].…”
Section: Introductionmentioning
confidence: 99%
“…Through the interaction between KIRs and certain HLA class I molecules, NK cells can protect healthy cells from spontaneous destruction by NK-cell-mediated cytolysis. As such, KIRs play a significant role in the control of the immune response, explaining the observed associations between certain KIR genes and the development of rheumatoid arthritis [5], psoriatic arthritis [6], infertility or abortion [7], as well ascontrol of HIV disease progression [8]. The degree of HLA/KIR compatibility may also determine the success rate of hematopoietic stem cell transplantation therapy for certain leukemias [9][10].…”
Section: Introductionmentioning
confidence: 97%